2018
DOI: 10.1002/anie.201806076
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Solid‐State Synthesis of Substituted Cyclobutanes Assisted by Pseudorotaxane‐like MOFs

Abstract: Regioselective photodimerization of trans-4-styrylpyridine (4-spy) derivatives is performed using pseudorotaxane-like Zn-based metal organic frameworks MOFs as templates. The formation of rctt-HT (head-to-tail) dimers is achieved by confining pairs of coordinated 4-spy derivative ligands within hexagonal windows and then irradiating them with UV light. It is also possible to achieve a photodimerization reaction where two different substituted 4-spy ligands are included in such a MOF material. The ether bond fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 51 publications
(19 reference statements)
0
48
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] However, a loss of these functionalities in aqueous electrolytes (strong acid or alkali) severely limits application of MOFs in energy-related electrocatalysis. [1][2][3][4][5][6][7][8] However, a loss of these functionalities in aqueous electrolytes (strong acid or alkali) severely limits application of MOFs in energy-related electrocatalysis.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8] However, a loss of these functionalities in aqueous electrolytes (strong acid or alkali) severely limits application of MOFs in energy-related electrocatalysis. [1][2][3][4][5][6][7][8] However, a loss of these functionalities in aqueous electrolytes (strong acid or alkali) severely limits application of MOFs in energy-related electrocatalysis.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Single-crystal X-ray diffraction analysis showed that BIF-91 crystallized in P21/c space group in which each Co 2+ center adopts a CoN 4 O 2 distorted octahedral coordination geometry and is bonded by four (4) nitrogen atoms in B(im) 4 − ligands and two O atoms in ndc 2− linker (Figure 1a, and Table S1, Supporting Information). In the BIF-91 framework, the six-coordinated and five-connected center is linked with ndc 2− and B(im) 4 − ligands into a 3D porous framework ( Figure 1b). Importantly, as demonstrated in Figure 1c, there are obvious CH···π interactions between the ndc 2− linker and B(im) 4 − ligands in the channel.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
See 3 more Smart Citations